Prevalence of diabetes mellitus and its risk factors among the suburban population of Northwest Nigeria - Anas Ahmad Sabir; Salisu Balarabe; Abubakar Atta Sani; Simeon A Isezuo; Kabiru Sada Bello; Abdulgafar O Jimoh; Sandra O Iwuala (Sahel Medical Journal, 2017)
>Background: Diabetes mellitus (DM) was previously considered to be rare in sub-Saharan Africa. However, the prevalence is on the increase mainly because of urbanization and changes in lifestyle.Aim: The aim of our study was to determine the prevalence of DM and its correlates in the suburban population of Northwest Nigeria.Materials and Methods: A cross-sectional community-based study was carried out. Two hundred and eighty participants were recruited using a multistage sampling technique. Interviewer-administered questionnaire was utilized in obtaining demographic data from the participants. Anthropometric variables, fasting plasma glucose (FPG), and blood pressure measured using standard guidelines. The diagnosis of DM was based on the WHO guidelines.Results: The mean age was 42.3 ± 10.7 years. The overall prevalence of DM was 4.3% (males 4.5% and females 4.0%). The mean FPG was higher in the females (5.9 ± 1.2 mmol/L) than males (5.8 ± 2.5 mmol/L) though the difference was not statistically significant (P = 0.81). Obesity and increasing age were the major risk factors for DM among the suburban population.Conclusion: DM is common in suburban areas of Northwest Nigeria. We recommend increased awareness of the epidemic potential of this public health problem even in suburban areas.